The method of (Descriptive) and (Comparison) in the historical writings of Mirza Mohammedamin Manguri: An Analytical Study - Qadir, Kamaran Mohammed; Ahmad, Marzea Hussen (Halabja University Journal, 2023)
This method is talking about the historical writings of Mirza Mohammed Amin Manguri among his too much methods only the methods of (Praise) and (Comaparability) is taken here. In Manguries methods description is defined as glimpse، detail note-taking، events and personalities، as well assessment and registering of them by the way of images، views، and thoughts of him that was noted in certain time and place. In Manguris methods comparability was a way for escaping from myopia، transcending history and matching of kurdish society. Manguri from that way by matching the historical situations and its similarities in the levels of single and society، the level of understanding and civilization of kurdish society brought to the fore، he didn’t stop the comparability only in his society but included all the human history، from here he showed the size of the issues and hoped to solve them in a certain time.